Plant Growth Promotion Diversity in Switchgrass-Colonizing, Diazotrophic Endophytes - Gushgari-Doyle, Sara; Schicklberger, Marcus; Li, Yifan V.; Walker, Robert; Chakraborty, Romy (Frontiers in Microbiology, 2021)
Endophytic nitrogen-fixing (diazotrophic) bacteria are essential members of the microbiome of switchgrass (Panicum virgatum), considered to be an important commodity crop in bioenergy production. While endophytic diazotrophs are known to provide fixed atmospheric nitrogen to their host plant, there are many other plant growth-promoting (PGP) capabilities these organisms demonstrate. The diversity of PGP traits across different taxa of switchgrass-colonizing endophytes is understudied, yet critical for understanding endophytic function and improving cultivation methods of important commodity crops. Here, we present the isolation and characterization of three diazotrophic endophytes: Azospirillum lipoferum R1C, Klebsiella variicola F10Cl, and Raoultella terrigena R1Gly. Strains R1C and F10Cl were isolated from switchgrass and strain R1Gly, while isolated from tobacco, is demonstrated herein to colonize switchgrass. Each strain exhibited highly diverse genomic and phenotypic PGP capabilities. Strain F10Cl and R1Gly demonstrated the highest functional similarity, suggesting that, while endophyte community structure may vary widely based on host species, differences in functional diversity are not a clearly delineated. The results of this study advance our understanding of diazotrophic endophyte diversity, which will allow us to design robust strategies to improve cultivation methods of many economically important commodity crops.